KARAKTERISASI DAN POTENSI BAKTERI ENDOFIT AKAR KOPI (Coffea sp) SEBAGAI PENGHASIL INDOLE ACETIC ACID (IAA) - Rizkiana Pratiwi, Esti; Mega Suryani, Elsa; Adi Wira Prasetya, Indra; Al Batati, Nadiah (Bio-Lectura : Jurnal Pendidikan Biologi, 2024)
The Endophytic bacteria as a biofertilizer agent can minimize the use of chemicals from synthetic fertilizers. The aim of this research was to study the density, diversity and ability of endophytic bacteria from coffee plants that have the potential to produce IAA. Root samples were obtained from coffee plants in UB Forest (UBF), Sumberwangi, Malang. The root samples were surface sterilized and then crushed with a blender. Endophytic bacteria were isolated and tested for their potential to produce IAA. The results obtained were 18 isolates of IAA-producing bacteria. KAA6 Isolate were produced the highest concentration of IAA of 10.73 ppm at 48 hours of incubation followed by KBA3 isolate which produced 12.78 ppm of IAA at 72 hours of incubation. The potential bacteria can be further optimized to be used as an eco-friendly biofertilizer agent.